Harmonization of the Faith-Based Approach and Inclusive Circular Economy (in Promoting the Success of Waste Management): A Case Study of the CSR Program Kampung Berseri by PT Pertamina Patra Niaga AFT El Tari - Buhari Ramadani; Raden Bagus Pandan Guritno; Satrio Lelono; Muhammad Iqbal Firdaus; Musdiyanto (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This study aims to explore how the CSR Program Kampung Berseri has created a harmonization between a faith-based approach and an inclusive circular economy in promoting the success and effectiveness of waste management in Kupang City. The research employed a qualitative method with a case study approach. Data were collected through interviews, CSR internal documents, and related literature. The findings indicate that the Gereja Masehi Injili di Timor (GMIT), as a Faith-Based Organization (FBO), has successfully established socio-spiritual legitimacy (as a foundation for transforming community behavior) through three main activities: (1) environmental training for church councils, (2) dissemination of information through church pulpits, and (3) the establishment of waste bank units within churches and schools (29 units in total) spread across 18 sub-districts in Kupang City. The success of the social legitimacy built by GMIT has reinforced the effectiveness of Bank Sampah Mutiara Timor in implementing an inclusive circular economy within the Kampung Berseri Program. This effectiveness is demonstrated by the production of 300 liters of eco-enzyme (100 bottles ready for sale), an increase in the number of active customers (78 individuals), outreach to 3,304 households with 99,947.6 kg of waste managed, 300 participants engaged in roadshow activities, and an increase in the waste bank’s income ranging from 20% to 180%.